Outcome stagnation of liver transplantation for primary sclerosing cholangitis in the Model for End-stage Liver Disease era - Klose, Johannes (Langenbeck's archives of surgery, 2014)
Purpose: Survival after liver transplantation (LTX) has decreased in Germany since the implementation of Model for end-stage liver disease (MELD)-based liver allocation. Primary sclerosing cholangitis (PSC) is known for its otherwise excellent outcome after LTX. The influence of MELD-based liver allocation and subsequent allocation policy alterations on the outcome of LTX for PSC is analyzed. Methods: This is a retrospective observational study including 126 consecutive patients treated with LTX for PSC between January 1, 1999 and August 31, 2012. The PSC cohort was further compared to all other indications for LTX in the study period (n = 1420) with a mean follow-up of 7.9 years (SD 3.2). Multivariate risk-adjusted analyses were performed. Alterations of allocation policy have been taken into account systematically. Results: Transplant recipients suffering from PSC are significantly younger (p < 0.001), can be discharged earlier (p = 0.018), and have lower 3-month mortality than patients with other indications (p = 0.044). The observed time on the waiting list is significantly longer for patients with PSC (p < 0.001), and there is a trend toward lower match MELD points in the PSC cohort (p = 0.052). No improvement in means of short-term mortality could be shown in relation to alterations of allocation policy within the MELD era (p = 0.375). Survival rates of the pre-MELD era did not differ significantly from those of the MELD era (p = 0.097) in multivariate risk-adjusted analysis. Patients in the MELD era suffered pre-transplant significantly more frequently from dominant bile duct stenosis (p = 0.071, p = 0.059, p = 0.048, respectively; chi2). Conclusions: Progress is stagnating in LTX for PSC. Current liver allocation for PSC patients should be reconsidered.
Gesehen am 23.10.2020